Assessing Multidimensional Energy Literacy of Secondary Students Using Contextualized Assessment - Chen, Kuan-Li; Liu, Shiang-Yao; Chen, Po-Hsi (International Journal of Environmental and Science Education, 2015)
Energy literacy is multidimensional, comprising broad content knowledge as well as affect and behavior. Our previous study has defined four core dimensions for the assessment framework, including energy concepts, reasoning on energy issues, low-carbon lifestyle, and civic responsibility for a sustainable society. The present study compiled a series of contextualized question items into a computer-based test (CBT) platform to examine students' energy literacy. Each test unit included a scenario, presented via multimedia materials (e.g., text, image, short video, and animation), that pertained to real-life situations. Various types of questions were employed (e.g., multiple true-false, multiple choice, and short-answer) that required students to construct responses and make judgments. A total of 1,711 secondary school students participated in this survey. The results indicate that the energy literacy level of Taiwanese secondary students is discouragingly low and inter-correlations between the dimensions of energy literacy reveal that energy knowledge and behavior are more closely correlated than affect and behavior. In addition, the scores on the attitudinal items were slightly higher for junior than senior students and the students in the southern region scored higher on energy literacy than those in other regions. These findings provide evidence for the future development of energy-related educational curricula and materials that can improve students' energy literacy and engagement in energy-related decisions.
Keywords: Age Differences; Computer Assisted Testing; Educational Technology; Energy; Energy Conservation; Foreign Countries; Geographic Location; Knowledge Level; Multimedia Materials; Multiple Choice Tests; Questionnaires; Scores; Secondary School Students; Statistical Analysis; Student Attitudes; Student Behavior; Student Surveys; Video Technology